(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2014)
The public areas, mainly those granted with green spaces and a vegetation cover offer several benefits to citizens, they do improve the well-being quality of life by ensuring the physical and mental health and guaranteeing a healthier environment where people can do outdoor activities, and are also important for the ecological conservation. In this work, the index of green spaces per habitant and their accessibility were calculated in order to assess the current situation and propose methodologies for urban planning that have been used on other countries. The results showed up that Puerto Bolívar has only one meter square of green spaces per habitant and that in some areas those are even absent. These values fall far below the standard index recommended by the World Health Organization (WHO, 1986). On the other hand, it is remarkable that through the “urban regeneration project” developed during recent years, some areas have been recovered supporting the integration and healthy leisure activities of the community.